Associations between neurofilament light chain levels, disease activity and brain atrophy in progressive multiple sclerosis - Szilasiova, Jarmila; Mikula, Pavol; Rosenberger, Jaroslav; Fedicova, Miriam; Urban, Peter; Frigova, Lydia; Vitkova, Marianna; Gdovinova, Zuzana; Hanes, Jozef; Stevens, Eva (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2022)
BACKGROUND: Neurofilament light chain is a promising biomarker of disease activity and treatment response in relapsing-remitting multiple sclerosis (MS). Its role in progressive MS is less clear. AIM: The aim of the study was to assess the relationship between plasma neurofilament light chain (pNfL) and disease activity as defined by the concept NEDA-3 (No Evident Disease Activity), and brain volumetry, in a cohort of patients with the progressive disease form (PMS). METHODS: Levels of pNfL (SIMOA technology) were examined in 52 PMS patients and analysed in relationship to NEDA-3 status and annual brain volume loss (BVL) during the last 12 months. The statistical model was developed using logistic regression analysis, including demographic, clinical and magnetic resonance imaging (MRI) data as independent variables. Dependent variables were NEDA-3 status and BVL. RESULTS: The mean age of the study participants (n=52, 50% females) was 45.85 (SD, 9.82) and the median disability score was 5.0 (IQR: 5.0-5.5). ROC analysis showed that pNfL predicts NEDA-3 (the sensitivity and specificity of the model were 77.8% and 87.6%, respectively, P<0.001) and abnormal BVL (the sensitivity and specificity were 96.6% and 68.2%, respectively, P<0.001). CONCLUSIONS: The results show that pNfL levels are a useful biomarker of disease activity determined by NEDA-3 status, including brain MRI-volumetry, in patients with the progressive form of MS.
Keywords: multiple sclerosis; Magnetic Resonance Imaging; Female; no evident disease activity; biologické markery; Central Nervous System Diseases; Biomarkers; ženské pohlaví; relabující-remitující roztroušená skleróza; intermediární filamenta; lidé; Multiple Sclerosis; magnetická rezonanční tomografie; roztroušená skleróza; mozek; progressive MS; atrofie; Male; progrese nemoci; Atrophy; Brain; nemoci centrálního nervového systému; Multiple Sclerosis, Relapsing-Remitting; Disease Progression; brain volume loss; Intermediate Filaments; mužské pohlaví; neurofilament light chain; Humans